Praktik Otoritas MUI Dalam Menjaga Kerukunan Umat Beragama Di Indonesia : Practice of the MUI Authority in Maintaining Religious Harmony in Indonesia - Tri Bambang Prasetyo; Wahyuddin Bakri (IAIN Parepare, 2023)
The scope of major issues regarding the harmony of religious life, namely the implementation of laws and regulations, especially Law No. 32 of 2004 concerning government difficulties in its implementation, the development of the religious sector including the five government affairs which are still in the hands of the government, this research tries to find out the practice of authority carried out by religious institutions, especially Islamic teachings as the majority religion in Indonesia, are seen as a sociological phenomenon. This research uses the method of a literature study, collecting library data and references starting from the internet, reading, taking notes, processing research. The collected data are scientific publications filtered by references to books, journal articles. identifying the results of the research referring to the problem